The surviving object : psychoanalytic clinical essays on psychic survival-of-the-object - Abram, Jan (Abingdon, Oxon ; New York, NY : Routledge, 2022)
In this book, Abram proposes and elaborates the dual concept of an intrapsychic surviving and non surviving object and examines how psychic survival-of-the-object places the early m/Other at the centre of the nascent psyche before innate factors are relevant. Abram's clinical-theoretical elaborations advance several of Winnicott's key concepts. Moreover, the clinical illustrations show how her advances arise out of the transference-countertransference matrix of the analyzing situation. Chapter by chapter the reader witnesses the evolution of her proposals that not only enhance an appreciation of Winnicott's original clinical paradigm but also demonstrate how much more there is to glean from his texts especially in the contemporary consulting room. The Surviving Object comprises 8 chapters covering themes such as: the incommunicado self; violation of the self; the paradox of communication; terror at the roots of non survival; an implicit theory of desire; the fear of WOMAN underlying misogyny; the meaning of infantile sexuality; the father in the nursing mother's mind' as an integrate' in the nascent psyche; formlessness preceding integration; a theory of madness. The volume will appeal to psychoanalysts and psychoanalytically-informed psychotherapists of all levels who are inspired by clinical psychoanalysis and the study of human nature.
Keywords: Winnicott, D. W. -- 1896-1971.; Object relations (Psychoanalysis); PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health